The politics of renewed quest for a Biafra Republic in Nigeria (2017)
The quest for a Biafran Republic by the Igbo ethnic group has become a recurring demand in Nigeria since the late 1960s. The agitation has been premised on claims of marginalisation and exclusion of the Igbo people in the Nigerian body politic. In spite of the consistency of the agitation through various Administrations, there was a noticeable lull in such demands during the time of President Goodluck Jonathan, only to assume a frightening proportion since the advent of the Administration of President Muhammadu Buhari. This article locates the factors in the outcomes of the 2015 general elections: the question of inclusion and representation; the unfinished nature of the Nigerian civil war; economic challenges, miscalculation both on the part of the Igbo people and indiscretion in the initial appointments made by President Muhammadu Buhari. The article recommends political restructuring of Nigeria as one of the ways to address secessionist tendencies